Pengaruh Model Problem Based Learning Terhadap Kemampuan Berpikir Kritis Peserta Didik Kelas Iv Pada Mata Pelajaran Pendidikan Pancasila Sekolah Dasar - Habsah Afifatul Amri; Syafrudin, Ulwan; Hariyanto; Destini, Frida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study was the low critical thinking skills of fourth grade students at SDN 1 Totokaton in Pancasila education subjects. This study aims to determine the effect of the problem-based learning model on students' critical thinking skills. This study is a quantitative study using a quasi-experimental method with a non-equivalent control group design. The population of this study consisted of 42 fourth-grade students at SDN 1 Totokaton. Sampling was conducted using a saturated sample technique. The research sample consisted of fourth-grade class A as the experimental class and fourth-grade class B as the control class. Data collection techniques included tests and non-tests. Data analysis techniques used simple linear regression tests. The results of the data analysis showed that there was a significant effect of the use of the problem-based learning model on students' critical thinking skills with a simple linear regression test that showed a significance of 0.001 ≤ 0.05.